Lean environmental management integration system for sustainability of ISO 14001: 2004 standard implementation - Perumal Puvanasvaran; Robert Kerk Swee Tian; Suresh A/L Vasu (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The purpose of this study is to present a model for integrating Lean Principles with ISO 14001 Environmental Management System. Design/methodology: To achieve the objective of the study, the methodology used in this study is based on preliminary literature review of ISO 14001 standards and Lean Principles as well as certain case reports from various proponents and authors of ISO 14001 and Lean as noted in various articles and journals and some books. Findings: The findings of this study are a new model called Lean Environmental Management Integration System (LEMIS) has been developed and leads to the creation of these measurement standards for evaluating the organization, making its environmental efforts more realistic, focused and attainable. Research limitations/implications: Future research should be conducted case studies in this direction are required to be conducted for examining the feasibility of amalgamation and implementing ISO 14001:2004 standards with the philosophy of Lean Principles to enable the achievement of world class standards. Practical implications: This model helps to eliminate any wasteful processes in the organization's implementation of the ISO 14001 standard thus leading to higher environmental performance. Integrating the standard with Lean principles through LEMIS model helps to specify these performance measures making the standard achieve sustainability and continual improvement. Originality/value: This study presents a unique approach of integrating the two main models, namely Lean Principles and ISO 14001 Environmental Management System, as a single framework benefiting contemporary organizations.
Keywords: 650; Lean Principles; EMS; ISO 14001; Integration; Continual improvement; Sustainability